Herbal teas heavy metal evaluation with renal function assessment in regular consumers in Benin - ALLABI, AUREL CONSTANT EUSTACHE; Adounkpe, Ferdinand (My University, 2017)
Herbal teas are openly sold in markets and main streets of big cities like Cotonou in Benin. Most people treat themselves at low cost with wide variety of herbal plants with proven therapeutic properties. The purpose of this research was to evaluate the content of heavy metals in herbal teas sold daily in Cotonou. In addition, we would evaluate if this heavy metal content of herbal teas could affect the renal function of regular consumers. Therefore, herbal teas samples were collected from selected sellers at well-known places. Samples’ analyses were done by reverse anodic stripping voltammetry with the Metalyser HM 3000 coupled to PC 101 NT pump. Biological markers of kidney failure in blood and urine of regular consumers were also assessed. Renal creatinine clearance and albuminuria were measured, the ratio of micro-albuminuria/creatininuria was calculated, and then red and white blood cells were counted. The results indicate that 7.69 and 30.77% of the herbal teas samples displayed an abnormal high concentration in cadmium (Cd) and lead (Pb) concentration, respectively. Statistical significant difference was found between the analyzed herbal tea samples in regard to Cd and Pb content (P ˂ 0.01). No obvious biological sign of severe kidney damage has been noted among regular consumers using their blood and urine samples. Only 8.60% of them had clearances between 60 and 89 ml/min/1.73 m2 with mild kidney failure. This study indicates that some herbal teas contain toxic chemicals such as Cd and Pb over recommended limits of 3 and 10 μg/L, respectively. The regular consumption of these herbal teas could be health threatening for the population.
Keywords: Herbal teas; heavy metals; environmental pollution; human renal function; anodic stripping; voltammetry.